Kinetics of the Sorption of Cobalt Onto Mg/Al Layered Double Hydroxide - Zhao, Donglin; Ding, Yi; Chen, Shaohua; Zhang, Kehua; Liu, Chen (Asian Journal of Chemistry, 2013)
The sorption behaviour of cobalt by Mg2Al layered double hydroxide (Mg2Al LDH) was investigated as a function of contact time under ambient conditions. The sorption of cobalt onto Mg2Al layered double hydroxide increases sharply within the first 1 h, then it rises slowly and reaches equilibrium in 5 h. The kinetic sorption is fitted by the pseudo-second-order model very well. The results manifest that Mg2Al layered double hydroxide is a promising material for the preconcentration and separation of pollutants from large volumes of aqueous solutions.